Pengaruh Penggunaan Media Sosial Pribadi terhadap Personal Branding Mahasiswa Komunikasi Digital dan Media - Anatasya Disha Nurhayati Siswanto; Hari Otang Sasmita; Rici Tri Harpin Pranata; Sutisna Riyanto (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
The rapid advancement of social media platforms has reshaped how people form and express their identities within digital environments, especially among university students. This research seeks to examine the extent to which personal use of social media influences the development of personal branding among students in the Digital Communication and Media Program at IPB University Vocational School. A quantitative research method with a survey approach was applied, involving 71 participants selected through random sampling techniques. Data collection was carried out using an online questionnaire employing a four-point Likert scale, and the data were analyzed through various statistical tests including validity and reliability assessments, classical assumption tests, Pearson correlation, simple linear regression, and determination coefficient using SPSS software. The results demonstrate that personal engagement with social media has a significant and positive relationship with students’ personal branding. Students who post consistently, produce high-quality content, and engage positively with audiences tend to project a stronger professional persona. Overall, the findings indicate that social media serves not only as a means of communication but also as an essential medium for developing one’s reputation and professional credibility in the digital age.